2018
DOI: 10.7554/elife.36898
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic progression, arrest, exit or death relies on centromere structural integrity, rather than de novo transcription

Abstract: Recent studies have challenged the prevailing dogma that transcription is repressed during mitosis. Transcription was also proposed to sustain a robust spindle assembly checkpoint (SAC) response. Here, we used live-cell imaging of human cells, RNA-seq and qPCR to investigate the requirement for de novo transcription during mitosis. Under conditions of persistently unattached kinetochores, transcription inhibition with actinomycin D, or treatment with other DNA-intercalating drugs, delocalized the chromosomal p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 75 publications
(112 reference statements)
2
27
0
1
Order By: Relevance
“…Retention of elongating RNAPII at centromeres has been observed in metaphase chromosomes of human, fly and frog cells (Blower, 2016;Chan et al, 2012;Molina et al, 2016;Rosic et al, 2014), and several roles for mitotic centromere transcription have been proposed (Blower, 2016;Chan et al, 2012;Liu et al, 2015). However, a recent study has questioned the role of mitotic transcription for accurate chromosome segregation (Novais-Cruz et al, 2018). Our results demonstrate that elongating RNAPII is passively retained at centromeres in mitosis as a byproduct of cohesin retention.…”
Section: Mitotic Centromere Transcriptionmentioning
confidence: 47%
See 1 more Smart Citation
“…Retention of elongating RNAPII at centromeres has been observed in metaphase chromosomes of human, fly and frog cells (Blower, 2016;Chan et al, 2012;Molina et al, 2016;Rosic et al, 2014), and several roles for mitotic centromere transcription have been proposed (Blower, 2016;Chan et al, 2012;Liu et al, 2015). However, a recent study has questioned the role of mitotic transcription for accurate chromosome segregation (Novais-Cruz et al, 2018). Our results demonstrate that elongating RNAPII is passively retained at centromeres in mitosis as a byproduct of cohesin retention.…”
Section: Mitotic Centromere Transcriptionmentioning
confidence: 47%
“…Importantly, this nascent-RNA signal on mitotic chromosomes in WAPL-AID cells was eliminated by treatment with triptolide, an inhibitor of RNAPII transcription initiation (Titov et al, 2011) (Fig. 2F-G), likely through RNAPII degradation following extended triptolide treatment (Novais-Cruz et al, 2018).…”
Section: Aid Cells Was Dependent On the Presence Of Cohesin As Co-depmentioning
confidence: 98%
“…Several studies show that inhibited transcription or splicing in mitosis or degradation of centromeric RNAs results in reduced CENP-C intensity on the kinetochore, anaphase extension, and chromosome segregation errors [22,[73][74][75]. However, a recent study suggested that transcription in mitosis was not required for mitotic progression in human cells [24]. The importance of transcripts in centromeric DNA has been reported for many species, including humans [75], maize [21,76], budding yeast [77], fission yeast [78], and flies [72].…”
Section: The Role Of Ncrnas In the Assembly And Function Of Kinetochoresmentioning
confidence: 99%
“…Since centromeric RNAs are transcribed and accumulated during mitosis [69,80], inhibiting transcription in mitosis affects kinetochore function [69,70]. However, a recent study suggested that transcription in mitosis was not required for mitotic progression [24]. The authors reported that DNA-intercalating drugs (α-amanitin) reduce localization of aurora-B in the centromere without reducing the amount of centromeric RNAs [24].…”
Section: The Role Of Ncrnas In the Assembly And Function Of Kinetochoresmentioning
confidence: 99%
See 1 more Smart Citation